Near real-time automated dose restoration in IMPT to compensate for daily tissue density variations in prostate cancer. (5th May 2017) - Jagt, Thyrza; Breedveld, Sebastiaan; van de Water, Steven; Heijmen, Ben; Hoogeman, Mischa
Abstract: Proton therapy is very sensitive to daily density changes along the pencil beam paths. The purpose of this study is to develop and evaluate an automated method for adaptation of IMPT plans to compensate for these daily tissue density variations. A two-step restoration method for 'densities-of-the-day' was created: (1) restoration of spot positions (Bragg peaks) by adapting the energy of each pencil beam to the new water equivalent path length; and (2) re-optimization of pencil beam weights by minimizing the dosimetric difference with the planned dose distribution, using a fast and exact quadratic solver. The method was developed and evaluated using 8–10 repeat CT scans of 10 prostate cancer patients. Experiments demonstrated that giving a high weight to the PTV in the re-optimization resulted in clinically acceptable restorations. For all scans we obtained V 95% ⩾ 98% and V 107% ⩽ 2%. For the bladder, the differences between the restored and the intended treatment plan were below +2 Gy and +2%-point. The rectum differences were below +2 Gy and +2%-point for 90% of the scans. In the remaining scans the rectum was filled with air, which partly overlapped with the PTV. The air cavity distorted the Bragg peak resulting in less favorable rectum doses.